Relationship of Superficial Scald Related Fruit Maturity with Polyphenoloxidase and Superoxide Dismutase Activities in Red Spur Delicious Apples - Akhtar Abbasi, Nadeem; M. Kushad, Mosbah; Ahmad Hafiz, Ishfaq; Maqbool, Mehdi (Asian Journal of Chemistry, 2010)
The paper demonstrates the possible relationship between scald and scald related maturity factors to the changes in activities of superoxide dismutase (SOD), peroxidase (POD) and polyphenol oxidase (PPO) in apple fruits during storage. Fruits from red spur delicious apples at early mature, full mature and over mature stages were harvested and shortly after harvest, stored at -1 °C. Fruits from each maturity stage were analyzed for enzymes activities (SOD, POD, PPO), ethylene synthesis, flesh firmness, soluble solids and starch contents at the time of harvest, during ripening at 2, 4 and 8 weeks intervals and then after 3, 4 and 5 months of storage. Higher scald index in immature fruits than mature fruits was recorded and that was increased with increase in storage duration, which corresponds with increased fruit softening and senescence. No change was found in POD activity with change in maturity at the time of harvest, but higher POD activity in immature fruits during storage compared to mature ones conflicts with such conclusion and may suggest no relationship between POD and scald development. However, the results of high scald incidence in immature fruits which were also high in PPO activity during storage and low in antioxidants (SOD) activity in immature fruits suggests a possible correlation between scald, PPO activity and antioxidant level.